Innovations and Emerging Therapies in Glaucoma - Wroten, Chris (Canadian Journal of Optometry, 2018)
It’s unclear when the progressive optic neuropathy that is glaucoma was first discovered, but it has been described in medical writings since ancient times. Hippocrates wrote of a blindness in the elderly that he called “glaykoseis.” Much later, the English ophthalmologist Richard Banister first discovered a correlation with high intraocular pressure (IOP). The invention of the ophthalmoscope by Hermann von Helmholtz in the mid-1800’s allowed the in vivo visualization of glaucomatous changes to the optic nerve for the first time, and in 1862 Franciscus Donders coined the term “Glaukoma simplex” to describe blindness resulting from elevated IOP. Shortly thereafter, the invention of the tonometer, the development of perimetry, and the use of cocaine as an anesthetic all further advanced the diagnosis of glaucoma.